Active literacy across the curriculum : connecting print literacy with digital, media, and global competence, K-12 - Jacobs, Heidi Hayes (New York, NY : Routledge, 2018)
Help students become more confident and successful readers, writers, and thinkers in today's world. In this new edition of a bestseller, highly acclaimed author and speaker Heidi Hayes Jacobs offers practical ideas for closing the literacy gap by teaching classic literacies (reading, writing, speaking, and listening) along with essential new literacies (digital, media, and global). The expanded second edition features Heidi's latest work on the new literacies and provides enhanced versions of strategies designed to help educators integrate critical language skills into their daily operational curriculum. These strategies include: Revising and expanding the role of all teachers so that they see themselves as classical language and contemporary literacy teachers; separating vocabulary into three distinctive types with distinctive instructional approaches to sustain and extend independent language development; building creative and visual notetaking and sketchnoting strategies; designing media projects for every class level and employing a consistent editing and revision policy for writing assignments; using a formal approach to develop speaking skills through four discussion types to increase civil public discourse; employing direct technical instruction that promotes the use of the human voice and body as a speaking and communication instrument; using Curriculum Mapping to develop formal benchmark assessments for active literacy and new literacy cultivation in every subject and on every level. Each chapter is focused on a specific strategy and includes practical examples so you can easily implement the ideas, no matter what grade level or subject area you teach -- Provided by publisher. -- Provided by publisher.
Introduction: Essential Strategies to Nurture the Literate Learner: Classical and Contemporary --Updating Roles: Every Teacher Becomes a Contemporary Literacy Teacher -- Developing Three Types of Words with Classical Approaches and Digital Tools -- Activating Notemaking: Extraction, Reaction, and Sketchnoting -- Editing and Revising Classical Writing and Media Production: A Consistent Developmental Policy to Support Student Independence -- Face to Face in Real and Virtual Space: Speaking, Listening, and Discussion Types -- Tuning the Speaking/Listening Instrument: Giving Voice Lessons in Each Classroom -- Activating Literacy in Our Plans: Upgrading Curriculum Maps K-12
"First edition published by Eye On Education 2006"--Title page verso.
Includes bibliographical references.
Keywords: Language arts -- Correlation with content subjects; Language experience approach in education; Direct instruction